Предмет: Алгебра,
автор: dratutii
cosx/1 + sinx + cosx/1-sinx
Ответы
Автор ответа:
0
Cosx/1 + sinx + cosx/1-sinx = cos x(1-sinx) + cosx(1+sinx) /(1+sinx)(1-sinx)=
=cosx - cosx*sinx + cosx + cosx*sinx / (1- sin^2x) = 2 cos x/ cos^2 x =
= 2/cos x
=cosx - cosx*sinx + cosx + cosx*sinx / (1- sin^2x) = 2 cos x/ cos^2 x =
= 2/cos x
Похожие вопросы
Предмет: Биология,
автор: lisavoigg208ggvp
Предмет: Химия,
автор: mallayaaaaaaa
Предмет: Математика,
автор: nikzero1
Предмет: Химия,
автор: Ксюшаша
Предмет: Обществознание,
автор: alinapan230504